Identification and characterization of the functional tetrameric UDP-glucose pyrophosphorylase from Klebsiella pneumoniae - Isabel Ramón Roth; Pavel Kats; Timm Fiebig; Françoise Routier; Roman Fedorov; Larissa Dirr; Jana I. Führing (mBio)
ABSTRACT In all kingdoms of life, the enzyme uridine diphosphate-glucose pyrophosphorylase (UGP) occupies a central role in metabolism, as its reaction product uridine diphosphate-glucose (UDP-Glc) is involved in various crucial cellular processes. Pathogens, including fungi, parasites, and bacteria, depend on UGP for the synthesis of virulence factors; in particular, various bacterial species utilize UDP-Glc and its derivatives for the synthesis of lipopolysaccharides, capsular polysaccharides, and biofilm exopolysaccharides. UGPs have, therefore, gained attention as anti-bacterial drug target candidates, prompting us to study their structure-function relationships to provide a basis for the rational development of specific inhibitors. UGP function is tied to its oligomeric state, and the majority of bacterial homologs have been described as tetramers encoded by the galU gene. Uniquely, enterobacterial species harbor a second gene, galF, encoding a protein with high homology to UGP, whose function is somewhat controversial. Here, we show that the galF gene of the opportunistic pathogen Klebsiella pneumoniae encodes a dimeric protein that has lost UGP activity, likely due to a combination of active site mutations and an inability to tetramerize, whereas the functional K. pneumoniae UGP, encoded by galU, is an active tetramer. Our AlphaFold-assisted structure-function relationship studies underline that tetramerization is essential for bacterial UGP function and is facilitated by a common mechanism utilizing conserved key residues. Targeting the respective molecular interfaces, which are absent in human UGP, could provide a means of selectively inhibiting the bacterial virulence factor UGP and potentially rendering pathogenic species avirulent.IMPORTANCEThe enzyme uridine diphosphate-glucose pyrophosphorylase (UGP) is important for the virulence of bacterial pathogens and, therefore, a potential drug target. In this study, we identify the gene encoding the functional UGP in Klebsiella pneumoniae, a bacterium notoriously causing severe antibiotic-resistant infections in humans, and reveal structural and functional features that may aid in the development of new antibiotics.